دور حامض اللايبوتكوك المنقى جزئيا من بكتريا E.faecalis المعزولة محليا في الالتصاق - عبد الكريم, لينة; فليح, مي طالب; شاكر, خمائل لطفي (Al-Nahrain Journal of Science, 2018)
The isolate E.faecalis U12 was tested for adhesion to Uroepithelial cells, the bacteria adhere in average of 81.25 (bacterial cell/ epithelial cell) .When the role of partial purified LTA was tested The adherence was inhibited by using 400 μg ⁄ml LTA and 500 μg ⁄ml LTA in a percentage of 8.5% and 10% respectively, these results refered to the secondary role of LTA in the adherence of E.faecalis. While it could not inhibit the adherence in 500 μg ⁄ ml dLTA, this refered to the role of lipid part of LTA in the adherence.